Where do high speed tennis serves come from? - Noffal, G. (coachesinfo.com)
About the stature of the athletes with the highest recorded serve speeds to date and the rackets for that. Especially are discussed: - Strings - Segment Rotations - Racquet Head Size (square inches) and String Tension (lbs) of Top 10 Men and Women - Shoulder & Elbow Loads in a Tennis Serve - Forces and torques of Interest - Implications for Injury - Injury prevention and - Ball spin